Characterization of newly prepared TiO2-chitosan/glass for the removal of a monoazo dye via the combination effect of photodegradation-adsorption - Zainal, Zulkarnain; Lee, Kong Hui; Hussein, Mohd Zobir; Abdullah, Abdul Halim; Hamadneh, Imad (Moh'd Khair) Rashid (Universiti Putra Malaysia Press, 2005)
The newly prepared TiO2-Chitosan/Glass is a promising alternative/complementary method to conventional means of wastewater treatment. Characterization of TiO2-Chitosan/Glass photocatalyst was studied with SEM-EDX, XRD, and FTIR analysis. The combination effect of photodegradation-adsorption process for the removal of methyl orange (MO), an acid dye of the monoazo series occur promisingly when 4 layers of TiO2-Chitosan/Glass photocatalyst was used for MO removal. FTIR study had confirmed the reactive –NH2, -OH, and metal oxide contents in the prepared photocatalyst responsible for the photodegradation-adsorption effect. Similarly, MO removal behavior was well supported by SEM-EDX and XRD analysis. A marked dependence of MO removal on the TiO2-Chitosan loading was observed and discussed. The research work done thus far suggests a new method, having both the advantages of photodegradation-adsorption process in the abatement of various wastewater pollutants.